2020
DOI: 10.1177/1534508420976830
|View full text |Cite
|
Sign up to set email alerts
|

Differential Item and Test Functioning of the SRSS-IE12 Across Race, Ethnicity, Gender, and Elementary Level

Abstract: This study used item response theory (IRT) methods to investigate group differences in responses to the 12-item Student Risk Screening Scale-Internalizing and Externalizing (SRSS-IE12) in a sample of 3,837 elementary school students. Using factor analysis and graded response models from IRT methods, we examined the factor structure, and item and test functioning of the SRSS-IE12. The SRSS-IE12 internalizing and externalizing factors reflected the hypothesized two-factor model. IRT analyses indicated that SRSS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
3
8
1
Order By: Relevance
“…The results support the use of the SAEBRS across grade levels (e.g., Kilgus, Eklund, et al, 2016). The results also align with previous DIF studies indicating small-to-negligible effects (Barger et al, 2022; Schatschneider et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results support the use of the SAEBRS across grade levels (e.g., Kilgus, Eklund, et al, 2016). The results also align with previous DIF studies indicating small-to-negligible effects (Barger et al, 2022; Schatschneider et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…However, the researchers found similar results to Lambert et al (2018) in that there was no significant DIF between Black and White students, but Black students were rated with lower mean scores (i.e., higher risk) than White students. All three studies found that teachers rated Black students were rated with higher mean risk compared to their non-Black peers, but there was minimal to small DIF (Barger et al, 2022; Lambert et al, 2018; Pendergast et al, 2017).…”
Section: Teacher Completed Screening Measures For Seb Riskmentioning
confidence: 98%
See 3 more Smart Citations